Microstructural, mechanical and corrosion behaviour of Al–Si alloy reinforced with SiC metal matrix composite. (December 2019) - Bandil, Kapil; Vashisth, Himanshu; Kumar, Sourav; Verma, Lokesh; Jamwal, Anbesh; Kumar, Devendra; Singh, Neera; Sadasivuni, Kishor Kumar; Gupta, Pallav
The aim of the present study is to investigate the effect of Si and SiC addition on the microstructure, mechanical, and corrosion properties of Al matrix-based composites. Al–Si (2 wt% fixed) alloy reinforced SiC composites were prepared by stir-casting process using SiC reinforcement contents from 0 to 20 wt% at an interval of 5%. A uniform dispersion of SiC particles in the Al matrix was observed from the scanning electron microscopic analysis. Maximum hardness is found for composites having 15 wt% reinforcement content. Pin-on-disc wear test reveals that SiC particles increase the wear resistance of composites. Corrosion test reveals that composites reinforced with 20% reinforcement content shows the minimum i corr among all the compositions, attributing to the maximum corrosion resistance. Tribological and corrosion behaviour were found to be dependent on the reinforcement content. However, they were not interdependent on each other. It is expected that the present study would be helpful in the development of lightweight composites for aerospace and shipping industries applications.